Intrauterine vertical SARS‐CoV‐2 infection: a case confirming transplacental transmission followed by divergence of the viral genome. (22nd March 2021) - Zaigham, M; Holmberg, A; Karlberg, ML; Lindsjö, OK; Jokubkiene, L; Sandblom, J; Strand, AS; Andersson, O; Hansson, SR; Nord, DG; Tannenberg, P
Abstract : This article includes Author Insights, a video abstract available at https://vimeo.com/bjog/authorinsights16682